Auditoría de seguridad física y lógica a los recursos de tecnología de información en la carrera informática de la ESPAM MFL - Loor Párraga, Amarilis Carolina (2014)
This research aims to evaluate the safety of existing resources information technology in the Computer Science of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, an audit of physical and logical security is performed between October 2013 and February 2014, for the purpose, the methodology established on the Auditing International Standards which is divided into three phases, the first one corresponds to the Planning and includes a comprehensive analysis of all the elements involved in the entity, complemented by the evaluation of internal control of regulation that is issued by the Controller General of the State, the second is the Execution where audit programs for components are applied and determined to be assessed, such as data integrity among others, in this section, there are evident the main findings raised in the entity. Finally, the Communication Result phase, where are described the conclusions and recommendations through presenting the Final Audit Report. With the results of the evaluation of internal control, it is determined that the audited entity applies general safety guidelines, a situation that is checked to obtain the Kendall concordance coefficient of 0.85, and the evaluated entity has a documented control of approved procedures, therefore recommended developing control regulations such as Security Policy, among others.